The Representamen of Psychological Awareness in The Main Character of The Film “A Man Called Otto” - Angga Armando; Sri Narti; Dilmai Putra (International Journal of Human Capital and Innovative Management, 2025)
Film is a powerful form of mass communication that conveys not only entertainment but also deep psychological and social messages. This study explores the representamen of psychological awareness in the main character, Otto, from the film “A Man Called Otto,” using Charles Sanders Peirce’s semiotic theory. The research applies a qualitative descriptive method by analyzing scenes and visual symbols that reflect Otto’s emotional journey from grief and isolation to social reconnection and healing. Otto’s character transformation is examined through Peirce’s triadic model: sign, object, and interpretant. The findings reveal that Otto’s psychological struggle—stemming from the trauma of losing his wife—manifests through defensive behavior, emotional detachment, and resistance to social bonds. However, through continuous interaction with neighbors and the support of his new social environment, Otto gradually regains emotional openness and self-awareness. The film employs visual metaphors, symbolic cues, and narrative structure to portray the healing process, emphasizing the role of social support and human connection in overcoming emotional pain. This study contributes to the intersection of film studies and communication psychology by showcasing how cinematic storytelling can represent and shape psychological experiences in a relatable and impactful way